Endogenous Money Supply Theories and Their Main Implications - Péter Aradványi; Zoltán Szalai (Financial and Economic Review)
Contrary to earlier exogenous approaches, it is now accepted, particularly among monetary experts, that the creation and the putting into circulation of money in modern financial systems is an endogenous process. However, there is still a significant delay in drawing a number of conclusions. This article presents what we consider to be the most important implications for the monetary policy toolbox, the implementation of monetary policy and international capital flows. An endogenous money creation approach can help to provide a more solid foundation for analyses and avoid possible economic policy mistakes.